2007
DOI: 10.1158/1055-9965.epi-06-0608
|View full text |Cite
|
Sign up to set email alerts
|

Fatalistic Beliefs about Cancer Prevention and Three Prevention Behaviors

Abstract: Background: A substantial proportion of US adults hold fatalistic beliefs about cancer prevention. Although evidence suggests that fatalistic beliefs discourage people from engaging in screening behaviors that can reduce their cancer risk, far less is known about associations between cancer fatalism and other prevention behaviors. We examined sociodemographic correlates of these beliefs and their associations with regular exercise, smoking, and fruit and vegetable consumption with a national sample of American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
341
5
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(372 citation statements)
references
References 34 publications
24
341
5
2
Order By: Relevance
“…While those who perceived themselves "not at all likely" to develop CKD may have been less likely to adhere to prescribed therapies due to a lack of perceived need, persons who perceived themselves as "very likely" to develop CKD may have had fatalistic attitudes about the benefit of adherence on adverse outcomes. Studies in other areas have demonstrated fatalistic attitudes regarding the inevitability of disease may contribute to poor adherence rates [31][32][33][34] and that persons who perceive their ability to control their health are better able to adhere to medical regimens for chronic illnesses. [35][36][37] Greater perceptions of risk might also be associated with other attitudes we did not measure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While those who perceived themselves "not at all likely" to develop CKD may have been less likely to adhere to prescribed therapies due to a lack of perceived need, persons who perceived themselves as "very likely" to develop CKD may have had fatalistic attitudes about the benefit of adherence on adverse outcomes. Studies in other areas have demonstrated fatalistic attitudes regarding the inevitability of disease may contribute to poor adherence rates [31][32][33][34] and that persons who perceive their ability to control their health are better able to adhere to medical regimens for chronic illnesses. [35][36][37] Greater perceptions of risk might also be associated with other attitudes we did not measure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also point to the problematic relationship between education and health behaviour. For example, fatalistic beliefs and doubt regarding the benefits of early diagnosis are more common among those with a lower SES, which can be, but is not necessarily, related to level of education (Niederdeppe & Levy 2007, Wardle et al 2004). The question is whether or not a general level of education could be a significant predictor, especially in the population of FB&H, where 77.4% of women have a low level of education (Institute for Statistics FB&H 2014) or whether the answer lies elsewhere.…”
Section: Athey Et Al 2011)mentioning
confidence: 99%
“…However, an overestimation of cancer risk can also lead to anxiety and unnecessary use of healthcare resources [35][36][37]. When perceived risk is greatly overestimated, particularly for breast cancer, women may be less likely to pursue screening indicating the adoption of a fatalistic view [38].…”
Section: Resultsmentioning
confidence: 99%
“…Fatalism, or the idea that a cancer diagnosis is inevitable, has been negatively associated with weekly exercise, smoking cessation and proper diet, raising the possibility that an adoption of this belief may indicate higher cancer risks due to poor health behaviors [38]. Additional studies into fatalism have found that African American women who hold more fatalistic attitudes less likely to follow breast cancer screening guidelines.…”
Section: Resultsmentioning
confidence: 99%